Agronomy and Environmental Sustainability of the Four Major Global Vegetable Oil Crops: Oil Palm, Soybean, Rapeseed, and Sunflower - Denis J. Murphy (Agronomy, 2025)
Four crops, oil palm, soybean, rapeseed, and sunflower, are collectively responsible for >91% of all globally traded vegetable oil production, worth an annual USD 223 billion. However, these crops fall into two distinctive categories with respect to their agronomy, yield, socioeconomic value, and overall sustainability. The dichotomy between perennial oil palm and the three annual oilseed crops is perhaps best shown in their relative efficiencies in oil production versus the amount of land that they occupy. Hence, land-friendly oil palm produces >90 Mt of oil on 29 Mha of land, with an average oil yield of 3.3 t/ha. In contrast, the three land-hungry annual crops collectively produce 121 Mt of oil on a huge land area of 191 Mha, giving a much lower average oil yield of 0.6 t/ha. In this study, the dichotomy between oil palm and the three major oilseed crops is examined further by comparing their respective carbon emission and uptake dynamics. The direct comparison of four such different crops is challenging, as much of the previous work has focused on single crops involving differing methodologies. The analysis therefore provides a novel perspective that enables several important conclusions to be drawn for policy decisions on the use of limited land resources. In particular, the sustainable production of vegetable oils needs to be reconsidered in the context of factors such as climate change, threats to food security, and the performance of the global economy.